The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1139/gen-2015-0168
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcoding as an aid for species identification in austral black flies (Insecta: Diptera: Simuliidae)

Abstract: In this paper, the utility of a partial sequence of the COI gene, the DNA barcoding region, for the identification of species of black flies in the austral region was assessed. Twenty-eight morphospecies were analyzed: eight of the genus Austrosimulium (four species in the subgenus Austrosimulium s. str., three species in the subgenus Novaustrosimulium, and one species unassigned to subgenus), two of the genus Cnesia, eight of Gigantodax, three of Paracnephia, one of Paraustrosimulium, and six of Simulium (sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
(28 reference statements)
1
7
0
Order By: Relevance
“…While well known (e.g. Crosskey 1990, Craig et al 2012 for simuliid female adults to be found long distances from flowing water, here, final association of immatures and adults will no doubt require further collecting, rearing, and molecular techniques (e.g., Joy & Conn 2001, Hernádez-Triana et al 2017. Based on head proportions, Simulium littosodalis and S. littosocius do not appear to be that closely related; S. littosocius possessing a markedly narrowed frons.…”
Section: Concluding Discoursementioning
confidence: 70%
“…While well known (e.g. Crosskey 1990, Craig et al 2012 for simuliid female adults to be found long distances from flowing water, here, final association of immatures and adults will no doubt require further collecting, rearing, and molecular techniques (e.g., Joy & Conn 2001, Hernádez-Triana et al 2017. Based on head proportions, Simulium littosodalis and S. littosocius do not appear to be that closely related; S. littosocius possessing a markedly narrowed frons.…”
Section: Concluding Discoursementioning
confidence: 70%
“…We expected higher levels of genetic variation between members of known species complexes, even though cytological studies were not carried out in our study [ 3 , 22 – 24 , 40 ]. With this regard, most of the specimens grouped together, and high levels of genetic diversity was not identified between species complexes.…”
Section: Discussionmentioning
confidence: 97%
“…The protocols of Hernández-Triana et al [ 3 , 24 ] were used to carry out all molecular work. When pupae were selected for analysis, most of the thorax, gill, and cocoon were retained as a voucher, while the pupal abdomen and/or the thoracic region (ventral side) were used for DNA extraction.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations